Effect of calcitonin gene-related peptide (-receptor) antibodies in chronic cluster headache: Results from a retrospective case series support individual treatment attempts. (December 2020) - Ruscheweyh, Ruth; Broessner, Gregor; Goßrau, Gudrun; Heinze-Kuhn, Katja; Jürgens, Tim P; Kaltseis, Katharina; Kamm, Katharina; Peikert, Andreas; Raffaelli, Bianca; Rimmele, Florian; Evers, Stefan
Objective: To assess the efficacy of monoclonal antibodies targeting calcitonin gene-related peptide (CGRP) or its receptor in chronic cluster headache (CCH) treatment under real world conditions. Background: Calcitonin gene-related peptide has an important pathophysiological role in cluster headache. Although the randomised controlled trial with the calcitonin gene-related peptide antibody galcanezumab was negative, chronic cluster headache patients with insufficient response to other preventive treatments have been receiving individual off-label treatment attempts with calcitonin gene-related peptide-(receptor) antibodies. Methods: Data from 22 chronic cluster headache patients who received at least one dose of a calcitonin gene-related peptide(-receptor) antibody and recorded attack frequency in a headache diary were retrospectively collected at eight headache centres. Results: The number of previous preventive therapies was 6.5 ± 2.4 (mean ± standard deviation, range: 2–11). The average number of attacks per week was 23.3 ± 16.4 at baseline and significantly decreased by −9.2 ± 9.7 in the first month of treatment with a calcitonin gene-related peptide(-receptor) antibody ( p  < 0.001). Fifty-five percent of the patients were 50% responders and 36% were 75% responders with respect to attack frequency. Significant reduction of attack frequency started at week 1 (−6.8 ± 2.8 attacks, p  < 0.01). Results were corroborated by significant decreases in weekly uses of acute headache medication (−9.8 ± 7.6, p  < 0.001) and pain intensity during attacks (−1.2 ± 2.0, numerical rating scale (NRS) [0–10], p  < 0.01) in the first month. In months 2 (n = 14) and 3 (n = 10), reduction of attack frequency from baseline was −8.0 ± 8.4 ( p  = 0.004) and −9.1 ± 10.0 ( p  = 0.024), respectively. Conclusion: Under real-world conditions, individual treatment with calcitonin gene-related peptide(-receptor) antibodies was effective in 55% of our chronic cluster headache patients. This finding supports individual off-label treatment attempts with calcitonin gene-related peptide-(receptor) antibodies in chronic cluster headache patients insufficiently responding to other therapies.